GAUSS-STEFFENSEN TYPE INEQUALITIES - Pečarić, Josip; Smoljak Kalamir, Ksenija (Matematichki Bilten, 2014)
In this paper we extend Gauss-Steffensen’s inequality to the class of functions that are “convex at point \(c\)”. As a consequence we obtain Gauss-Steffensen type inequality for convex functions. Further, we produce linear functional which generates exponential convexity and Stolarsky type means.